7 - Book Review: The Lugano Report: On Preserving Capitalism in the Twenty-First Century, with an Appendix and Afterword by Susan George, Pluto Press, London, Sterling (Virginia), 1999. Paperback, 213 pages.: by Claudio Schuftan - Claudio Schuftan (Africa Development, 1999)
Abstract